Historiographical reflection on the Malay World - Tatiana A. Denisova; Reviewed by: Hadenan Towpek, PhD (Al-Albab, 2015)
This work began with a very interesting criticism from the author, Tatiana A. Dnisova, who argued that: “every time there is a need to understand the Malay view on various subjects or areas of human life, a researcher must refer to primary sources, i.e. the Malay literary treasures, including works on the historiography of Islamic Malay. “